Development and characterization of a human monoclonal antibody targeting the N-terminal region of hepatitis C virus envelope glycoprotein E1 - Mesalam, Ahmed Atef; Desombere, Isabelle; Farhoudi, Ali; Van Houtte, Freya; Verhoye, Lieven; Ball, Jonathan; Dubuisson, Jean; Foung, Steven K.H.; Patel, Arvind H.; Persson, Mats A.A.; Leroux-Roels, Geert; Meuleman, Philip (Elsevier, 2018)
Monoclonal antibodies (mAbs) targeting the hepatitis C virus (HCV) envelope have been raised mainly against envelope protein 2 (E2), while the antigenic epitopes of envelope protein 1 (E1) are not fully identified. Here we describe the detailed characterization of a human mAb, designated A6, generated from an HCV genotype 1b infected patient. ELISA results showed reactivity of mAb A6 to full-length HCV E1E2 of genotypes 1a, 1b and 2a. Epitope mapping identified a region spanning amino acids 230-239 within the N-terminal region of E1 as critical for binding. Antibody binding to this epitope was not conformation dependent. Neutralization assays showed that mAb A6 lacks neutralizing capacity and does not interfere with the activity of known neutralizing antibodies. In summary, mAb A6 is an important tool to study the structure and function of E1 within the viral envelope, a crucial step in the development of an effective prophylactic HCV vaccine.